2011
DOI: 10.1103/physrevb.84.024206
|View full text |Cite
|
Sign up to set email alerts
|

Site preference and elastic properties of Fe-, Co-, and Cu-doped Ni2MnGa shape memory alloys from first principles

Abstract: The site preference and elastic properties of Fe-, Co-, and Cu-doped Ni 2 MnGa alloys are investigated by using the first-principles exact muffin-tin orbital method in combination with coherent-potential approximation. It is shown that Fe atom prefers to occupy the Mn and Ni sublattices even in Ga-deficient alloys; Co has strong tendency to occupy the Ni sublattice in all types of alloys; Cu atoms always occupy the sublattice of the host elements in deficiency. For most of the alloys with stable site occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 60 publications
4
48
0
Order By: Relevance
“…at 110 K in a field of 2 T. The value of μ s at 5 K for Ni 2 MnGa in the present study is in good agreement with the value reported by Ahuja et al [13]. Recently, Li et al investigated theoretically the site preference and elastic properties of Fe-, Coand Cu-doped Ni 2 MnGa alloys by using the first-principles exact muffin-tin orbital method in combination with the coherent-potential approximation [14]. According to the results of the calculation by Li et al [14] [14] are in good agreement with those reported earlier for the stoichiometric Heusler alloy Ni 2 MnGa [15][16][17][18][19][20][21][22].…”
Section: Methodssupporting
confidence: 92%
See 4 more Smart Citations
“…at 110 K in a field of 2 T. The value of μ s at 5 K for Ni 2 MnGa in the present study is in good agreement with the value reported by Ahuja et al [13]. Recently, Li et al investigated theoretically the site preference and elastic properties of Fe-, Coand Cu-doped Ni 2 MnGa alloys by using the first-principles exact muffin-tin orbital method in combination with the coherent-potential approximation [14]. According to the results of the calculation by Li et al [14] [14] are in good agreement with those reported earlier for the stoichiometric Heusler alloy Ni 2 MnGa [15][16][17][18][19][20][21][22].…”
Section: Methodssupporting
confidence: 92%
“…The antiferromagnetic coupling between nearest-neighbor Mn atoms in Ni 2 (Mn 1 − y Cu y )(Ga 1 − y Mn y ) alloys is due to the variation of the exchange interaction that becomes antiferromagnetic for small Mn-Mn interatomic distances. This antiferromagnetic coupling was already proved experimentally and theoretically in many Mn-rich Ni-Mn-Ga Heusler alloys [14,[23][24][25][26][27]. Then, the μ s of Ni 2 (Mn 1 − y Cu y )(Ga 1 − y Mn y ) alloys is given by μ s (cal) = 2μ Ni + (1 − y)μ MnI + yμ Cu + (1 − y)μ Ga + yμ MnII , where μ MnI and μ MnII mean the values of the magnetic moment of the Mn atoms on the Mn sublattice and the Ga sublattice, respectively.…”
Section: Methodssupporting
confidence: 53%
See 3 more Smart Citations